STUDI PERBANDINGAN TINGKAT PEMAHAMAN SISWA PADA PEMBELAJARAN FIQIH ANTARA KELAS DIGITAL DAN KELAS REGULER DI MAN 2 ACEH TAMIANG - Darmayanti, Alfina; Fitriani, F (Institut Islam Mamba'ul 'Ulum Surakarta, 2025)
This research aims to compare the level of students' understanding in Fiqh subjects between digital classes and regular classes. As educational technology continues to develop, it is important to evaluate the effectiveness of these learning methods. The type of research used is quantitative research with an experimental approach. The research was conducted at MAN 2 Aceh Tamiang involving 50 students divided into two groups: 25 students from digital classes and 25 students from regular classes. Data was collected through a comprehension test consisting of 20 multiple choice questions and interviews which aimed to find out students' opinions about the learning experience of digital classes and regular classes. The analysis results show that students in digital classes have a higher level of understanding compared to students in regular classes, with an average score of 80.60 for digital classes and 72.00 for regular classes. This research concludes that the use of technology in Fiqh education can significantly increase students' understanding. These findings provide recommendations for integrating more digital elements in the learning process in madrasas.